Childhood trauma-related alterations in brain function during a Theory-of-Mind task in schizophrenia - Quidé, Yann; Schnell, Knut (Schizophrenia research, 2017)
Childhood trauma is a risk factor for schizophrenia that affects brain functions associated with higher cognitive processes, including social cognition. Alterations in Theory-of-Mind (ToM), or mentalizing skills, are a hallmark feature of schizophrenia, and are also evident in individuals exposed to childhood trauma. However, the impact of childhood trauma exposure on brain function during social cognition in schizophrenia remains unclear. We thus examined the association between childhood trauma and brain function during the performance of a ToM task in 47 patients diagnosed with schizophrenia or schizoaffective disorder. All participants completed the Childhood Trauma Questionnaire (CTQ) and underwent functional magnetic resonance imaging while performing an established visual-cartoon affective ToM task. Whole-brain multiple regression analysis was performed on ToM-related brain activation, with CTQ total score as regressor of interest, while accounting for the effects of age, sex, diagnosis, symptom severity, behavioural performance, intelligence and medications levels. First, using a small-volume correction approach within a mask made of key regions for ToM [including bilateral temporo-parietal junctions (TPJ), medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC)/precuneus], total CTQ scores were positively associated with activation of the PCC/precuneus. Second, exploratory analyses for the rest of the brain (i.e., ROIs masked-out), revealed a positive association between trauma exposure and activation of the dorsomedial prefrontal cortex (dmPFC), and a negative association with activation of the anterior section of the TPJ. These results suggest that childhood trauma exposure may, at least partially, contribute to functional alterations of brain regions essential for effective mental state inference in schizophrenia.